Prognostic significance of red cell distribution width in hospitalized older patients with heart failure or infection. Issue 10 (8th August 2019) - Nakashima, Keitaro; Ohgami, Eiichi; Kato, Kazuhiko; Yoshitomi, Souichi; Maruyama, Toru; Harada, Mine
Abstract : Aim: Red cell distribution width (RDW) is a simple, sensitive and cost‐effective parameter, and is associated with pathophysiology of many common diseases. The aim of the present study was to investigate the prognostic role of RDW in older adults hospitalized for the treatment of heart failure (HF) or infection, because both diseases are fatal, especially in the geriatric population. Methods: This observational study consecutively enrolled 196 Japanese older (aged ≥75 years) patients hospitalized for the treatment of HF (group A, n = 102) or non‐cardiovascular bacterial infection (group B, n = 94). Baseline and clinical data were extracted from medical records. The observational period was that of hospitalization. The primary end‐point was classified in the order of discharge to the patients' home, discharge to other facilities and in‐hospital death. Results: Longer hospital stay ( P  < 0.01) and worse prognosis ( P  < 0.01), including higher in‐hospital mortality, were found in patients showing RDW ≥15% relative to those with RDW <15% in both groups. RDW showed no in‐hospital variation despite successful treatment of acutely decompensated HF in selected patients of group A ( n = 64). Conclusions: The present study showed the role of RDW in predicting the prognostic outcome of older adults hospitalized for the treatment of HF or infection, indicating that RDW is a stable and reliable parameter in these common diseases.Geriatr Gerontol Int 2019; 19: 988–992 .